2010
DOI: 10.1242/jeb.042937
|View full text |Cite
|
Sign up to set email alerts
|

Polarization sensitivity in two species of cuttlefish –Sepia plangon(Gray 1849) andSepia mestus(Gray 1849) – demonstrated with polarized optomotor stimuli

Abstract: SUMMARYThe existence of polarization sensitivity (PS), most likely resulting from the orthogonal arrangement of microvilli in photoreceptors, has been proposed in cephalopods for some time, although it has rarely been examined behaviourally. Here, we tested the mourning cuttlefish, Sepia plangon, and the reaper cuttlefish, Sepia mestus, for polarization sensitivity using a largefield optomotor stimulus containing polarization contrast. Polaroid filter drums with stripes producing alternating e-vectors were rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…At 30days, at least half of the cuttlefish responded to the polarization pattern at all velocities, except for the highest rotation rate of 130degs -1 (Fig.3). Previous studies demonstrated an OMR to polarized stripes in other mature cuttlefish species, using a velocity of 12degs -1 and with stripes 2.5cm in width (Talbot and Marshall, 2010a;Talbot and Marshall, 2010b), which raises the possibility that our cuttlefish would have responded to slower rotating patterns as well. However, Darmaillacq and Shashar (Darmaillacq and Shashar, 2008) did not succeed in eliciting an OMR to a polarized pattern in adult Sepia elongata, using velocities ranging from 34 to 178degs -1 , although S. elongata possess orthogonal photoreceptors in their retina suggesting the ability for polarization detection.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…At 30days, at least half of the cuttlefish responded to the polarization pattern at all velocities, except for the highest rotation rate of 130degs -1 (Fig.3). Previous studies demonstrated an OMR to polarized stripes in other mature cuttlefish species, using a velocity of 12degs -1 and with stripes 2.5cm in width (Talbot and Marshall, 2010a;Talbot and Marshall, 2010b), which raises the possibility that our cuttlefish would have responded to slower rotating patterns as well. However, Darmaillacq and Shashar (Darmaillacq and Shashar, 2008) did not succeed in eliciting an OMR to a polarized pattern in adult Sepia elongata, using velocities ranging from 34 to 178degs -1 , although S. elongata possess orthogonal photoreceptors in their retina suggesting the ability for polarization detection.…”
Section: Discussionmentioning
confidence: 82%
“…These apparently puzzling results could be explained by the higher speed of motion for the rotating pattern compared with the nearly stationary prey. In such a case, using a slowly moving pattern (Talbot and Marshall, 2010a;Talbot and Marshall, 2010b) might elicit stronger responses even in very young animals. Alternatively, these apparently contradicting results can be due to differences in the size of the receptive fields of the retina needed to detect each type of signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, moving gratings (similar to the Broadclub hunting display) and visual playback of looming patterns (similar to S. apama agonistic displays and Octopus chromatic pulses) have been used extensively to study the visual capabilities of a wide range of animal species, including cephalopods themselves (e.g., Talbot and Marshall, 2010; Temple et al, 2012). These experimental methods are designed to stimulate the motion detection system of the animal viewing the stimulus, and it seems likely that the natural dynamic displays of cephalopods have evolved for a similar purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The polarization sensitivity (PS) in two species of cuttlefish; Sepia plangon and Sepia mestus using wide-field optomotor stimuli were studied (Talbot and Marshall , 2010). Construction of model of computer for studying the visual system in cephalopods (Octopus, cuttlefish and squid), that have single unfiltered photoreceptor mechanism was discussed (Stubb and Stubbs, 2016).…”
Section: Introductionmentioning
confidence: 99%